CO2 hydrogenation on Co/CeO2-δ catalyst: Morphology effect from CeO2 support. (16th October 2020) - Xie, Fengqiong; Xu, Shiyu; Deng, Lidan; Xie, Hongmei; Zhou, Guilin
Abstract: The Co/CeO2-δ catalysts with different morphology structure were prepared for CO2 catalytic hydrogenation reaction. The physical and chemical properties of these catalysts were characterized by H2 -TPR, XRD, TEM, ICP and H2 -TPD. The characterization results indicated that the different morphology structure of CeO2 support obviously influence the exposed crystal plane, and then affect the concentration of oxygen vacancies, the metal-support interaction and the dispersion of Co 0 active species on the CeO2 support. In addition, the Co ions can be dissolved into the CeO2 lattice to form Ce–O–Co solid solution, which promotes the formation of Co 0 active species, oxygen vacancies, and the Ce 3+ -□-Co 0 structure, thus significantly affects the CO2 hydrogenation performance of Co/CeO2-δ catalysts. The exposed {110} and {100} crystal plane of CoCe140 catalyst with nano-rods structure ensure the excellent CO2 hydrogenation performance, including CO2 conversion is 48.7%, the CH4 and CO selectivity are 91.7% and 8.3%, respectively. Graphical abstract: The CO2 molecules can be effectively hydrogenated to HCOO − intermediate species, which can form CO and be further hydrogenated to CH4 . The oxygen vacancies and high dispersed Co 0 species on the Co/CeO2-δ catalysts are the main active species to catalyze the CO2 hydrogenation reaction. The studied catalysts with different morphology structure of the CeO2 support will deeply affect the CO2 hydrogenation reaction by affecting the concentration of oxygen vacancies, metal-support interaction and dispersion of Co 0 species when the Co species contact with different crystal plane of CeO2 support, which is critical to the formation of active centers. Image 1 Highlights: The properties of active Co can be affected by the morphology structure from CeO2 . The CeO2 {110} crystal plane can form abundant oxygen vacancies as active centers. Enriched oxygen vacancies enhance the Co 0  dispersion and metal-support interaction. The CO2  conversion reaches 48.7% although the amount of Co species is 1.0 wt %.